Who Drives Stock Trading? Analyzing the Impact of Foreign and Local Ownership on Transaction Value - Said Aryonindito; Farhatun Nisa (International Journal of Management and Business Economics, 2025)
This study examines the trust of market participants by analysing the dynamics of transaction value as an indicator of the perception of changes in foreign and local ownership. This study discusses the difference in impact between institutional and individual ownership. This study involves five variables where transaction value is the dependent variable and foreign ownership and local ownership are the independent variables. We also reduce the independent variables into institutional (corporate) and individual forms, respectively. The results show that all independent variables have a significant impact on transaction value but only individual local ownership has a negative direction.